THE SIGNIFICANCE OF ARMS AND AMMUNITION ON THE CAPE'S NORTHERN FRONTIER AT THE TURN OF THE 18TH CENTURY (Historia, 2021)
In the second half of the 18th century the expansion of the white settlement at the Cape became, primarily for geographical reasons, an eastward movement; thus the shifting eastern frontier has been well scrutinized historically. Apart from P.J. van der Merwe's seminal study, 1) the northern border has only recently come to the notice of historians in what may be termed a scientific fashion; the works of Robert Ross2) and Martin Legassick3) are pioneering efforts dealing with his frontier zone. Though this area did not experience the continuous and wide-scale contact between black and white polities that gave the eastern border its particular significance, nevertheless it of- fers the researcher rich rewards in the form, for example, of fresh insights into race relations and the "civilizin,g" role of the missionaries.